Sensor Use in Cruciate-Retaining Total Knee Arthroplasty Compared with Posterior-Stabilized Total Knee Arthroplasty: Load Balancing and Posterior Femoral Rollback - Song, Sang Jun; Kim, Kang Il; Park, Cheol Hee (The Journal of Knee Surgery, 2021)
The purpose was to investigate the proportion of severe load imbalance after appropriate conventional gap balancing and analyze the intraoperative kinematics after load balancing in cruciate-retaining (CR) and posterior-stabilized (PS) total knee arthroplasties (TKAs). In total, 45 sensor-assisted CR and 45 PS TKAs using NexGen prosthesis were prospectively evaluated. After appropriate conventional gap balancing, the loads at 10, 45, and 90 degrees of knee flexion were evaluated with a wireless load sensor placed in trial implants. The proportion of severe load imbalance (medial load–lateral load >75 lbs) was investigated. After load balancing, location of the femorotibial contact point was investigated at each flexion angle to analyze femorotibial kinematics. The proportion of the severe load imbalance was significantly higher in CR TKAs at the 10 degrees knee flexion (37.8 vs. 15.6%, p = 0.031). This proportion was higher in CR TKAs than in PS TKAs at the 45 and 90 degrees knee flexion angles, but without statistical significance (31.1 vs. 15.6%, p = 0.134 and 33.3 vs. 15.6%, p = 0.085, respectively). After load balancing, consistent posterior femoral rollback occurred in medial and lateral compartments during 90 degrees flexion in CR TKAs (p < 0.001), but not in PS TKAs. Medial pivot kinematics was not observed in both TKA designs. The sensor was more beneficial in CR TKAs for achieving appropriate load balancing and consistent posterior femoral rollback compared with PS TKAs. Further studies are required to identify target load distribution to restore ideal knee kinematics after TKA. This study shows level of evidence II.
Keywords: knee; arthroplasty; sensor; load; kinematics